Applications of Microscopy in Additive Manufacturing. Issue 4 (7th September 2015) - Weissmayer, Lisa; Schubert, Tim; Bernthaler, Timo; Schneider, Gerhard
Abstract Additive manufacturing (also known as 3D‐printing) is a new and promising method for the production of components in tool engineering. Its layer‐by‐layer build‐up process offers a number of new production possibilities. Of special interest is the high geometric and constructive freedom. It is possible to build up near net shape components with complex geometries and integrated functional properties, such as curved cooling channels in drills. Besides microstructural defects that significantly degrade the usage properties of components, the challenges faced in additive manufacturing are: the high level of dimensional accuracy required; surface quality; and the construction of complex tools with inner structures like cooling channels. Taking the example of additively manufactured indexable insert drills with curved cooling channels, we will show the suitability of microscopic methods for evaluating the quality of components produced in this way.